The effect of inorganic pigment on the tensile properties of polycarbonate irradiated with UV – light - AL-Shammary, Z. R. (Iraqi Journal of Physics, 2021)
The effect of UV-light on the tensile properties of pure PC has been studied. It was shown that irradiation of PC undergo a drop in the tensile properties of 30 hour of exposure. The results of irradiated samples shows that the addition of ZnO and TiO2 with different percentages (0.5, 1, 1.5 %) will reduce the Young modulus and ultimate stress of PC/ZnO ,PC/ TiO2 composites